A Sociopragmatic Study of Cooperative Principles in a Group of Middle-Aged Women’s Conversation - Revita, Ike; Kharismadewi, Yonnie; Lesmana, Sabtra (Center of Language and Cultural Studies [CLCS], 2021)
Communication is a way to interact with others and also a process of delivering information from the speaker to a hearer. In formal communications, Grice's cooperative principles tend to be recommended to be applied in a certain context. This research is aimed at identifying the use of cooperative principles by middle-aged women when having interaction in the kitchen at the wedding party. The research is conducted by using a qualitative approach in 2 regencies in West Sumatera Indonesia. The data were recorded and also note-taken in the field toward 27 women selected by purposive sampling. These women were around 45-60 years old. The interview was conducted with one Bundo Kandung, three customs leaders, and two intellectual people. The aspects related to context and politeness became the consideration in analyzing the data. The results showed that only two forms among the four maxims at cooperative principle used by the middle-aged women when they had communication in the kitchen at the wedding party. They are 1) the maxim of quantity and 2) the maxim of quality. A number of utterances were violating the maxim in cooperative principles. A number of utterances found are categorized as violations of the maxims if it is based on Grice’s theory. However, that does not apply to the utterances in a group of middle-aged women in Minangkabau during the cooking tradition. It is because there are social and cultural contexts that must be considered when understanding and analyzing these utterances.